The Cascode LNA with RF Amplifier at 5.8GHz Using T-Matching Network for WiMAX Applications - Ibrahim, Abu Bakar; Othman, Abdul Rani; Husain, Mohd Nor; Johal, Mohamad Syahrir; Hamidon, J. Sam (UTEM, 2012)
This paper presents the Cascode LNA with RF amplifier at 5.8GHz using T-matching network applicable for WIMAX application. The Cascode LNA uses FHX76LP Low Noise SuperHEMT FET and RF amplifier use EPA018A. The LNA designed used T-matching network consisting of lump element reactive element at the input and the output terminal. The Cascode LNA with RF amplifier produced gain of 36.4 dB and noise figure (NF) at 1.3dB. The input reflection (S11) and output return loss (S22) are -12.4dB and -12.3 dB respectively. The bandwidth of the amplifier is more than 1.2GHz. The input sensitivity is compliant with the IEEE 802.16 standards.